KRT18 Modulates Alternative Splicing of Genes Involved in Proliferation and Apoptosis Processes in Both Gastric Cancer Cells and Clinical Samples - Chen, Biao; Xu, Ximing; Lin, Dan-dan; Chen, Xin; Xu, Yang-tao; Liu, Xin; Dong, Wei-guo (Frontiers in Genetics, 2021)
Keratin 18 (KRT18), one of the most abundant keratins in epithelial and endothelial cells, has been reported to be aberrantly expressed in many malignancies and extensively regarded as a biomarker and important regulator in multiple cancers, including gastric cancer (GC). But the molecular regulatory mechanisms of KRT18 in GC patients and cells are largely unknown. In the present study, we analyzed the expression level of KRT18 in 450 stomach adenocarcinoma tissue samples from TCGA database and found a significant higher expression level in tumor tissues. We then explored the potential functions of KRT18 in AGS cells (human gastric adenocarcinoma cell line) by KRT18-knockdown using siRNA and whole transcriptome RNA-seq analysis. Notably, KRT18 selectively regulates expression of cell proliferation and apoptotic genes. Beyond this KRT18 affects the alternative splicing of genes enriched in apoptosis, cell cycle and other cancer related pathways, which were then validated by RT-qPCR approach. We validated KRT18-KD promoted apoptosis and inhibited proliferation in AGS cells. We then used RNA-seq data of gastric cancer samples to further demonstrate the modulation of KRT18 on alternative splicing regulation. These results together support the conclusion that KRT18 extensively modulates diverse alternative splicing events of genes enriched in proliferation and apoptosis processes. And the dysregulated splicing factors at transcriptional or post-transcriptional level by KRT18 may contribute to the alternative splicing change of many genes, which expands the functional importance of keratins in apoptotic and cell cycle pathways at the post-transcriptional level in GC.